ANALISIS MESIN PEMIPIH MELINJO MENGGUNAKAN MOTOR LISTRIK ½ HP DENGAN VARIASI KECEPATAN PUTARAN - M Rozak Ardiyanto; Xander Salahudin; Sri Widodo (Wahana Ilmuwan, 2017)
Melinjo (Gnetum gnemon L) is one of plantation crops are quite numerous in the island of Java. All parts of this plant can be used, especially “melinjo”seeds that can be processed into melinjo. Efforts to meet the needs of export are often hampered by the high level of orders, but less can be offset by craftsmen, because the manufacturing processes are done manually (by hand). Need to do a business improvement order “melinjo”production rate can be increased so as to meet consumer needs without reducing the quality of the result. Based on these problems, the research about how the influence of variation the round of the machine time flat. This research was conducted by comparing the engine performance flat with variations of each round of 15 rpm, 20 rpm and 30 rpm. The work principle of the machine is to utilize the electrical energy is converted into energy by the motor rotating and the subsequent rounds to the gearbox by using v-belt. Gearbox used have value ratio 1:50. Round gearbox forwarded to the dish not a flashlight. Then from the disk is not transmitted to the wheels small flashlight. Then of small wheels forwarded flat pipe. By harnessing the power of the dish not to be flattened pipe flashlight with full force. It is intended that “melinjo”that goes into the mold table can flat by flatten pipe. The result of this research is the optimal rotational speed was at 30 rpm. The results of the thickness of the nicest on a 30 rpm rotation that is with an average thickness of 1.75 mm. Flat engine capacity “melinjo” best at a speed of 30 rpm, with the data was 1,086 kg / hour.